2023
DOI: 10.3390/jcm12031211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endophthalmitis on the Risk of Acute Myocardial Infarction in Ankylosing Spondylitis Patients: A Population-Based Retrospective Cohort Study

Abstract: Many studies have demonstrated an increased cardiovascular (CV) risk in ankylosing spondylitis (AS) patients. Nevertheless, the influence of an endophthalmitis episode toward the future risks of acute myocardial infarction (AMI) in AS patients has been unclear. The objective of this study was to explore the impact of endophthalmitis on AMI risk in this particular patient population by a population-based retrospective cohort study with a follow-up period up to 16 years. Univariate and multivariate Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The global longitudinal peak systolic strain as a marker for subclinical myocardial dysfunction is lower in patients with AS [ 68 ]. Another interesting study showed an association with endophtalmitis and new onset of myocardial infarction [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The global longitudinal peak systolic strain as a marker for subclinical myocardial dysfunction is lower in patients with AS [ 68 ]. Another interesting study showed an association with endophtalmitis and new onset of myocardial infarction [ 69 ].…”
Section: Resultsmentioning
confidence: 99%